THE HISTORICAL PERIODISATION OF THE EDUCATION AND UP_BRINGING PROCESS OF CHILDREN AND YOUNG PEOPLE IN THE EDUCATIONAL AND CULTURAL INSTITUTIONS AT THE TERRITORY OF VOLYN AT THE 19th - FIRST HALF OF THE 20th CENTURY - Marchuk, O.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The article elaborates the historical periodization of the process of education and upbringing of children and young people in educational and cultural institutions of Volyn in the XIX - the first half of the 20th century and presents the ways of its using in educational institutions of today. It is said that the pedagogical experience of the past contributes to the improvement of educational systems. It is substantiated that the development of historical periodization of the process of education and upbringing of youth in the cultural and educational institutions of Volyn in the XIX - early XX century contributes to the systematization of scientific knowledge about the formation of the school system in Western Ukraine, approves the development of education in the region in the context of the development of the educational system of all Ukraine. It was noted that the problems of periodization of the educational systems of Ukraine were investigated in the scientific works of Y. Bulaka, N. Gupan, V. Kuril, O. Suhomlinskaya. The author has used various methods: the method of periodization; comparative analysis; method of generalization and concretization. On the basis of the analysis of educational policy implemented in the work of cultural and educational societies of Volyn of the XIX - early XX century three main historical stages of education and upbringing of the young generation in the territory of Volin were distinguished: a) 1800-1917 - staying of school under the influence of the Russian government policy ; b) 1917-1921 - the period of nationalization of the Volyn education system; c) 1921-1939 - the implementation of educational reforms under the auspices of the Second Commonwealth of Poland. The process of education and upbringing of young people in the studied periods is analyzed in detail. The studying used archival materials about the activities of educational institutions, religious societies, public organizations. The developed periodization made it possible to state the fact that the process of education and upbringing of young people in the cultural and educational institutions of Volyn in the 19th - beginning of the 20th centuries took place in the conditions when Ukraine was part of the Russian state, the Ukrainian People's Republic, the Ukrainian state and the Second Commonwealth of Poland. It was explained that during this time Ukrainians were raising the younger generation in the national spirit. It is stated that the developed periodization should be used in the analysis of the cultural development of Ukraine in higher and secondary education institutions.